Proceso de atención de enfermería en paciente adulto con neumotórax traumático CIE10 J939. - Lucas Parra, Sergio Iván (2022)
Thoracic trauma is a very difficult condition in emergency management. Of all deaths due to trauma, 75% are attributed a large percentage of these to complications such as pneumothorax root cause or contributing factor, this is the reason why the management of these chest injuries is essential in urgent interventions and hospital admission. Pneumothorax is the leakage of air from the lungs and in turn the presence of this air filling the space between the outer wall of the lung and the chest wall, pressure on the lungs, which prevents the normal expansion of the lungs. The main objective of this investigative case study is to apply the nursing care process for the management of pneumothorax presented in a 23-year-old patient, caused by a knife injury, received by the emergency personnel of the Martin Icaza Hospital, the This work prioritizes the nursing interventions applied in the management of these cases. Nursing interventions are vital in the recovery of the patient, through assistance and patient care practices during their hospital stay through the use of functional pattern assessment through the Nanda, Nic and Noc taxonomies, applied to the patient to your recovery.